Maximum Power Point Tracking Charge Controller for Standalone PV System - Mohd Asri Jusoh; Mohammad Faridun Naim Tajuddin; Shahrin Md Ayob; Mohd Azrik Roslan (Universitas Ahmad Dahlan, 2018)
The depletion of conventional energy sources and global warming has raised worldwide awareness on the usage of renewable energy sources particularly solar photovoltaic (PV). Renewable energy sources are non-polluting sources which can meet energy demands without causing any environmental issues. For standalone PV systems, a low conversion efficiency of the solar panel and high installation cost due to storage elements are the two primary constraints that limit the widespread use of this system. As the size of the system increases, the demand for a highly efficient tracking and charging system is very crucial. Direct charging of battery with PV module will results in loss of capacity or premature battery degradation. Furthermore, most of the available energy generated by the PV module or array will be wasted if proper tracking technique is not employed. As a result, more PV panels need to be installed to provide the same output power capacity. This paper presents selection, design and simulation of maximum power point tracker (MPPT) and battery charge controller for standalone Photovoltaic (PV) system. Contributions are made in several aspects of the whole system, including selection of suitable converter, converter design, system simulation, and MPPT algorithm. The proposed system utilizes direct duty cycle technique thus simplifying its control structure. MPPT algorithm based on scanning approach has been applied by sweeping the duty cycle throughout the I-V curve to ensure continuous tracking of the maximum power irrespective of any environmental circumstances. For energy storage, lead acid battery is employed in this work. MATLAB/Simulink® was utilized for simulation studies. Results show that the propose strategy can track the MPPs and charge the battery effectively.